Multi-Period Hierarchical Optimization for Der Dispatch in Tso-Dso Coordinated Networks - Garcia-Munoz, F (IEEE Computer Society, 2025)
This study proposes a hierarchical optimization model to coordinate Distributed Energy Resources (DERs) dispatch between Transmission System Operators (TSOs) and Distribution System Operators (DSOs), aiming to minimize operational costs, enable multi-period economic dispatch, optimize storage operations, and facilitate clean energy markets. In this regard, the TSO-DSO coordination is formulated as a bilevel optimization problem, where medium-voltage distribution networks (MV-DNs) act as leaders, optimizing DER operation based on load consumption and defining energy requirements for the TSO. The high-voltage transmission network (HV-TN) functions as a follower, dispatching DERs to meet the energy demands set by the MV-DNs. The DC optimal power flow (OPF) formulation is used to model HV-TN constraints, while the second-order cone relaxation of AC-OPF represents the MV-DN limitations. To address the nested complexity of the model, the Karush-KuhnTucker (KKT) conditions and the Big-M method are applied to convert the bilevel problem into a single-level problem, making it computationally tractable. The model is tested on the IEEE 30-bus system for the HV-TN and the IEEE 33-bus system for the MV-DNs. The results demonstrate the model s effectiveness in minimizing operational dispatch without voltage or congestion issues, with boundary variables satisfying equality constraints. © 2025 IEEE.